Second medical opinion in oncological setting. (April 2021) - Maruzzo, Marco; La Verde, Nicla; Russo, Antonio; Marchetti, Paolo; Scagnoli, Simone; Gonzato, Ornella; Di Maio, Massimo; Zagonel, Vittorina; Galvano, Antonio; Lanzetta, Gaetano; Perrone, Francesco; Beretta, Giordano; et al.
Highlights: The second opinion is increasingly requested by both doctors and cancer patients. It involves severe diagnosis, choice of treatment or communication difficulties. Few studies have addressed this issue with no general consensus. Our decalogue can be a useful tool to deal with the second opinion request. Abstract: Oncological patients increasingly require second medical opinions to feel more likely confident with their oncologists and treatments, although this could lead to wrong opinions and delay in the start of treatments. Second opinions can be required also by physicians to obtain advices, especially in case of rare tumors. The request of new opinions is documented in radiology and pathology settings too, with not negligible discrepancy rate. Conversely, the role in general medical/surgical conditions has not been well established. Literature is poor of studies relative to second opinions or they are more focused on patient's motivations. For these reasons, AIOM (Italian Association of Medical Oncology) and AIOM Foundation faced this topic during the 7th Annual Meeting on Ethics in Oncology (Ragusa, 4–5 t h May 2018). In this position paper we report reasons, limits, advantages and outcomes of second medical opinion and the respective Decalogue in the oncological setting.